SPATIAL DISTRIBUTION OF SURFACE SALINITY AND TEMPERATURE IN BREBES SEAWATER USING SPATIAL ANALYSIS TOOLS â INVERSE DISTANCE WEIGHTED : ITS EFFECTS ON THE OTHER WATER QUALITY PARAMETERS - Gemilang, Wisnu Arya; Wisha, Ulung Jantama (GEOMATIKA, 2017)
ABSTRACTThe coast of Brebes is an important area for fishing activities. Along the coast of Brebes, there are mangrove conservation areas which part of green belt development program of Java Northern Coast. The purpose of this study was to determine the influence of salinity and temperature to the water quality conditions by employing a spatial analysis method. The measurement of water quality conducted by employing purposive sampling method. The sampling data was taken in the same time of 1 tide condition which forecasted before. The data were analyzed statistically and spatially using inverse distance weighted analysis. Temperature values ranged from 29.4 to 31.8 Â°C, conductivity ranged from 3.53 â 4.71 S.m-1 with, pH ranged from 8.04 to 8.52, DO ranged from 3.18 to 6.57 mg.L-1, salinity ranged between 22.9 â 32.8 â°, the value of salinity, temperature, and water quality parameters showed that the distribution is not uniform. It is influenced by the physical dynamics of sea water, which has an severe impact on the environment changes. Salinity and temperature have an impact to conductivity and DO variability but they are not affect the pH value. DO and pH value is higher than the previous research in Brebes waters.Keywords: brebes, coastal, spatial analysis, water qualityÂ ABSTRAKPesisir Brebes merupakan kawasan yang penting bagi aktivitas perikanan. Disepanjang pantai Brebes terdapat kawasan konservasi mangrove yang merupakan program pembangunan kawasan sabuk hijau Pantai Utara Jawa. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh salinitas dan temperature terhadap kondisi kualitas perairan dengan menggunakan analisis spasial. Pengukuran sampel air dilakukan dengan metode purposive sampling, pengambilan data berdasarkan peramalan pasang surut. Analisa data dilakukan secara statistic dan spasial dengan menggunakan analisa inverse distance weighted. Nilai suhu berkisar antara 29.8 â 31.8Â°C, konduktivitas berkisar antara 3.53 â 4.71 S.m-1, pH berkisar antara 8,52 â 8,04, DO berkisar antara 3.18 â 6.57 mg.L-1, salinitas berkisar antara 22.9 â 32.8 â°. Nilai dari salinitas, temperature dan parameter kualitas perairan menunjukkan bahwa sebaran konsentrasinya tidak merata yang dipengaruhi oleh dinamika fisis air laut dan keberadaan sungai-sungai utama yang berdampak pada perubahan lingkungan. Salinitas dan temperature memiliki dampak terhadap variasi konduktivitas dan DO, namun tidak terlalu berpengaruh terhadap nilai pH. DO dan pH mengalami peningkatan konsentrasi bila dibandingkan dengan penelitian sebelumnya di perairan Brebes.Kata Kunci: analisis spasial, brebes, kualitas air, pesisir, pencemaran